Ni(OH)(2)-Fe2O3/CNOs ternary nanocomposite designed as an anode with complementary properties for high-performance li-ion battery - Dwivedi, Pravin Kumari; Muniraj, Vedi Kuyil Azhagan; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemistryselect, 2018)
Synthesis of the new ternary hybrid composite with excellent electrochemical performances for Li-ion battery is demonstrated. The ternary hybrid composite of Ni(OH)(2)-Fe2O3/Carbon Nano Onions (NFOC) is synthesized by using two-step solution phase method delivers a high reversible discharge capacity of 928 mAhg(-1) at 50 mAg(-1) and 673 mAhg(-1) at a higher current density of 1000 mAg(-1) with excellent rate performance. Additionally, it shows to have stable cycle life up to 1000 cycles with 96% capacity retention and more than 99% of coulombic efficiency. The synergetic effect between Ni(OH)(2), Fe2O3 and carbon nano onions (CNOs) as well as the unique feature of heterostructures are responsible for the improved electrochemical performance of the battery. The reversible reaction of Fe2O3 and Ni(OH)(2) with Li, maintains its long cycle life with higher reversible discharge capacity and CNOs improve the efficient electronic transfer, accommodate substantial volume expansion and maintain the structural integrity of the material during lithiation-delithiation process.
Keywords: Heterostructures; Long cycle stability; Superior rate capability; Ternary Composite; Transition metal oxides

High-energy flexible supercapacitor-synergistic effects of polyhydroquinone and RuO2 center dot xH(2)O with microsized, few-layered, self-supportive exfoliated-graphite sheets - Muniraj, Vedi Kuyil Azhagan; Dwivedi, Pravin Kumari; Tamhane, Parikshit Shivaji; Szunerits, Sabine; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Applied Materials & Interfaces, 2019)
An effective and straightforward route for tailoring the self-supporting, exfoliated flexible graphite substrate (E-FGS) using electrochemical anodization is proposed. E-FGS has essential features of highly exfoliated, few-layered, two-dimensional graphite sheets with the size of several tens of micrometers, interconnected along the axis of the substrate surface. The novel hierarchical porous structural morphology of E-FGS enables large active sites for efficient electrolyte ion and charge transport when used as electrode material for a supercapacitor. In order to effectively utilize this promising E-FGS electrode for energy storage purpose, a ternary composite is further synthesized with pseudocapacitive polyhydroquinone (PHQ) and hydrous RuO2 (hRO). hRO is synthesized via a sol-gel route, while electropolymerization is utilized for the electrodeposition of PHQ over E-FGS. Ultimately, the fabricated self-supporting E-FGS-based flexible supercapacitor is capable of delivering areal specific capacitance values as high as 378 mF cm(-2) at a current density of 1 mA cm(-2). Addition of the pseudocapacitive component to the E-FGS texture leads to similar to 10 times increase of the electrochemical charge storage capability. The imposition of mechanical forces to this flexible supercapacitor device results in trivial changes in electrochemical properties and is still capable of retaining 91% of the initial specific capacitance after 10 000 cycles. Alongside, the fabricated symmetrical solid-state flexible device exhibited a high energy density of 8.4 mu Wh cm(-2). The excellent performance along with the ease of synthesis and fabrication process of the flexible solid-state supercapacitor device using PHQ/hRO/E-FGS holds promise for large-scale production.
Keywords: graphite exfoliation; polyhydroquinone; ruthenium oxide; solid-state flexible supercapacitor; Ternary Composite

Electrospun nanofibers of Tin phosphide (SnP0.94) nanoparticles encapsulated in a carbon matrix: a tunable conversion-cum-alloying lithium storage anode - Yadav, Poonam; Malik, Wahid; Dwivedi, Pravin Kumari; Jones, Lathe A.; Shelke, Manjusha V. (Energy & Fuels, 2020)
Anodes with improved Li storage capability are required for next-generation lithium batteries. In this work we report a convenient synthesis strategy, based on electrospinning followed by reduction and phosphorization, to prepare a tin phosphide (SnP0.94) phase in a carbon nanofiber matrix. The layered structure offered by the SnP0.94 phase, along with its small size (5-20 nm) encapsulated in the conducting carbon matrix, leads to promising electrochemical Li storage characteristics. This composite has a capacity of 750 mAh g(-1) at 100 mA g(-1) with good cycling and rate stability. Electrochemical studies revealed a faster diffusion coefficient (1.86 x 10(-11) cm(2) s(-1)) for Li in the composite compared to the bare SnP0.94 (8.57 x 10(-14) cm(2) s(-1)), confirming the promise of this class of materials for cation storage in battery anodes.

Architecture of NaFe(MoO4)2 as a novel anode material for rechargeable lithium and sodium ion batteries - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Praveen, C. S.; Dwivedi, Pravin Kumari; Karbhal, Indrapal; Gosavi, Suresh W.; Shelke, V, Manjusha; Kale, Bharat B. (Applied Surface Science, 2021)
In recent decades, particular focus has been given to enhance the capacity of LIBs and SIBs either by developing new materials or by modifying existing materials. Hence, we have demonstrated a new anode material i.e. sodium iron molybdate [NaFe(MoO4)2] for both LIBs and SIBs. NaFe(MoO4)2 has been successfully synthesized by solid-state combustion technique and tested as a promising new anode material for both LIBs and SIBs. A detailed analysis of the crystal structure has been performed using DFT calculations. NaFe(MoO4)2 crystallizes in the monoclinic phase with the space group C2/c (#15). FESEM also shows highly crystalline monoclinic shaped crystals of micron size. When evaluated as an anode material for LIBs, NaFe(MoO4)2 electrode exhibited electrochemical capacity of 920 mAhg- 1 in the second cycle at the current density of 50 mAg-1. Though capacity decreases on further cycling, the coulombic efficiency was maintained at 99% for 50 cycles. Significantly, a high discharge capacity of 100 mAhg- 1 was maintained at a very high rate of 1 Ag-1. On the other hand, we have also tested NaFe(MoO4)2 for SIBs which shows excellent reversible specific capacity i.e. 100 mAhg- 1 at the current density of 100 mAg-1 even after 500 cycles. This novel system has shown good stability for LIBs and SIBs which is hitherto unattempted.
Keywords: Electrochemical study; lithium-ion battery; Morphology; NaFe(MoO4)2; Sodium-ion battery

Engineering microstructure of LiFe(MoO4)(2) as an advanced anode material for rechargeable lithium-ion battery - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Dwivedi, Pravin Kumari; Praveen, C. S.; Karbhal, Indrapal; Shelke, V, Manjusha; Kim, Bomyung; Park, Chinho; Kale, Bharat B. (Journal of Materials Science-Materials In Electronics, 2021)
Graphite is considered as an ideal anode material for lithium-ion battery (LIB) due to its high stability, good conductivity and wide source of availability. However, the low energy density and theoretical capacity of graphite cannot meet the needs of high performance anode materials. To circumvent this issue, alternative materials have been sought for many years now. Herein, we report the synthesis of highly crystalline lithium iron molybdate LiFe(MoO4)(2) by combustion method and evaluated its performance as an anode material for lithium-ion batteries. Triclinic LiFe(MoO4)(2) crystals having particle size 2-5 mu m with good crystallinity were obtained. The material shows long cycle life and high rate performance than commercial graphite and exhibits first reversible discharge capacity of 931.6 mAh/g at a current density of 100 mA/g which is three times higher than commercial graphite. The high specific capacity together with the outstanding rate and cycle performance makes LiFe(MoO4)(2) a promising anode material for LIB. A detailed analysis on the crystal structure and electronic properties of LiFe(MoO4)(2) is presented based on DFT studies to complement the experimental observations.

3D x-ray microtomography investigations on the bimodal porosity and high sulfur impregnation in 3D carbon foam for Li-S battery application - Thripuranthaka, M.; Chaturvedi, Vikash; Dwivedi, Pravin Kumari; Torris, Arun; Shelke, V. Manjusha (Journal of Physics-Energy, 2022)
Lithium-sulfur (Li-S) batteries, regarded as one of the most promising alternatives to current state-of-the-art rechargeable Li-ion battery technologies, have received tremendous attention as potential candidates for next-generation portable electronics and the rapidly advancing electric vehicle market. However, substantial capacity decay, miserable cycle life, and meagre stability remain critical challenges. More specifically, shuttling of polysulfide (Li2S (x) (3 < x <= 8)) species severely hinders the cycle performance resulting in capacity fade and cycling instability. In the present work, a highly conducting three-dimensional (3D) carbon nanofiber (CNF) foam has been synthesized using the lyophilization method followed by thermal pyrolysis. The highly porous foam materials have a bimodal porosity distribution in the nano and micro regime and were successfully investigated to serve as a potential host for sulfur species intended for Li-S battery application. 3D x-ray microtomography was employed to estimate the nature of sulfur impregnation and distribution in the 3D porous networks. On utilizing the final product as cathode material, sulfur impregnated carbonized CNF foam and modified the separator with functionalized multiwalled carbon nanotubes delivered a specific capacity of similar to 845 mAh g(-1) at 100 mA g(-1).
Keywords: bimodal porosity; CNF foam; Li-S battery; microtomography